Opportunities and implications of digital transformation: business, development, and work in the digital age - Mention, Anne-Laure (Henry Stewart Talks, 2022)
Digital transformation, Digitization, Digitalization, The emergence of new industries, business models and markets, The role of digital technologies in tackling grand challenges, The human side of digital transformation, The societal implications of digital transformation